Analisis Yuridis Kebijakan Politik Luar Negeri Indonesia Dalam Mendukung Kedaulatan Palestina Perspektif Siyasah Dauliyah - Monica Putri Syakira; Luthfi Fahrul Rizal; Muhammad Amin (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2027)
This study analyzes Indonesia's foreign policy in supporting Palestinian sovereignty through juridical aspects and the Siyasah dauliyah perspective. With an analytical descriptive method with a normative juridical approach, The results indicate that Indonesia's support possesses strong juridical legitimacy, aligning with constitutional mandates and the "independent and active" foreign policy principle against colonialism. Substantially, from a Siyasah dauliyah viewpoint, this policy reflects values of justice (al-‘adl), public interest (maslahah), and defense of the oppressed (nusrah al-mustadh’afin). Indonesia consistently prioritizes international diplomacy for Palestinian independence as a national legal responsibility and an implementation of Islamic political ethics. Consequently, this policy reinforces Indonesia’s commitment to achieving global peace based on justice. Such support represents a harmonious blend of constitutional obligations and universal moral principles to eliminate all forms of colonialism worldwide sustainably.